Influential factors of apricot market supply in Kandahar, Afghanistan - Hashimi, Sardar Mohammad; Mohd Nawi, Nolila; Man, Norsida; Ahmadzai, Khal Mohammad (Inderscience Publishers, 2022)
This study focused on factors influencing apricot market supply in Kandahar, Afghanistan with specific objectives to determine the most influential factors influencing apricot market supply. A multi-stage method of sampling was employed to select required apricot sample farmers. Five villages were purposively selected and 102 farmers were surveyed. Explanatory factor and multiple regression analyses were applied. Factor analysis revealed seven underlying factors such as, storage availability, market and variety information, access to credit, cost minimisation, logistical efficiency, price awareness and extension services. These factors were able to explain 79.8% of the variance in the analysis. Based on regression analysis, storage availability, logistical efficiency, price awareness, extension services and farm size were found as the most significant. Findings of the study suggest that the availability of storage, access to credit, extension and other services should be provided by the government to improve effective production and marketing of apricot supply.